Generating arrays of nanoring structures : chemical lithography with 2-dimensional polymeric colloidal crystals - Zhao, Qin (2014)
Nanoring arrays have attracted extensive research interest due to the novel and promising applications in a wide range of scientific fields. The limitations of existing fabrication techniques encourage the search for a new method to fabricate nanoring arrays which preserves easy process control and flexible tunability of nanoring geometries. This thesis demonstrates a simple and versatile approach for the fabrication of nanoring arrays by applying polymeric nanosphere monolayers as the templates. Arrays of well-defined polymeric nanoring features can be obtained by simply treating the template monolayers with molecules which can form disordered molecular networks on the substrate. Formation of nanoring structures is mainly realized by the interpenetration and attractive interactions between such molecular networks and the loosely entangled surface chains due to relaxation of the template nanospheres. Since the treatment molecules act as bridges to anchor surface polymer chains on substrate surface, these molecules are named as ‘bridging molecules’ in this thesis work. The feasibility to transfer the polymeric nanoring patterns into arrays of gold nanoring structures has also been demonstrated, indicating the potential applications of this fabrication technique to produce functional nanoring arrays composed of other materials. The versatility of this technique has been proven by forming nanoring arrays with alternative bridging molecules, template nanospheres and supporting substrates. Based on a systematic study about the formation mechanisms, some prerequisites for successful formation of nanoring structures have been established. Besides, the nanoring morphologies were shown to be affected by the treatment condition of bridging molecules, molecular structures of template nanospheres, and surface properties of substrates. A linear relationship between the nanoring diameter and the square root value of the template nanosphere size is derived based on geometrical calculations and experiment verification. Therefore, change in the sizes of the template nanospheres will result in simultaneous change in the diameters of nanoring structures and the lattice constants of nanoring arrays. In addition, vapor annealing or thermal annealing has been carried out to accelerate the relaxation of the template nanospheres and facilitate fast formation of nanoring arrays. Manipulation of the nanoring geometries can be achieved due to the form factor change of the template nanospheres upon annealing. By tailoring the relaxation of template nanospheres based on acetone vapor annealing, formation of multi-ring structures has been demonstrated.